Microstructures and high-temperature self-lubricating wear-resistance mechanisms of graphene-modified WC-12Co coatings - Haoliang Tian; Changliang Wang; Mengqiu Guo; Yongjing Cui; Junguo Gao; Zhihui Tang (Friction)
Abstract To reduce the friction coefficient of cobalt-cemented tungsten carbide (WC-12Co) wear-resistant coatings, graphene was compounded into WC-12Co powder via wet ball milling and spray granulation. Self-lubricating and wear-resistant graphene coatings were prepared via detonation gun spraying. The presence, morphologies, and phase compositions of graphene in the powders and coatings that are obtained through different powder preparation processes were analyzed. The analysis was performed using the following technologies: energy-dispersive X-ray-spectroscopy (EDXS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy. The mechanical properties of the coatings were studied using a microhardness tester and a universal drawing machine. The friction and wear properties of the coatings were studied using an SRV-4 friction and wear tester. The results showed that the graphene content in the WC-12Co coating modified with graphene was higher than that without modification; graphene was embedded in the structure in a transparent and thin-layer state. The adhesive strength of this coating at approximately 25 °C was approximately 60.33 MPa, and the hardness was approximately 984 HV0.3. After high-temperature treatment, the adhesive strength and hardness of the graphene oxide (GO)/WC-12Co coating decreased slightly (the lowest adhesive strength of 53.16 MPa was observed after treatment at 400 °C, and the lowest hardness of approximately 837 HV0.3 was observed after treatment at 300 °C). Compared to the friction coefficient (0.6) of the WC-12Co coating obtained at room temperature, the friction coefficient of the GO/WC-12Co coating was decreased by approximately 50% of that value. The graphene-modified coating was continuously exposed to the wear tracks on the surface of the contacting materials during friction, and a lubricating film was formed in the microareas in which the wear tracks were present. The coating exhibited improved self-lubricating and wear-resistant effects compared to the unmodified WC-12Co coating. The results of this study demonstrated that graphene could be effective in self-lubrication and wear-reduction in a temperature range of 100–200 °C, as a friction coefficient of 0.3 was maintained.